Normothermic Ex Vivo Kidney Perfusion for Human Kidney Transplantation: First North American Results. Issue 9 (1st March 2022) - Mazilescu, Laura I.; Urbanellis, Peter; Kim, S. Joseph; Goto, Toru; Noguchi, Yuki; Konvalinka, Ana; Reichman, Trevor W.; Sayed, Blayne A.; Mucsi, Istvan; Lee, Jason Y.; Robinson, Lisa A.; Ghanekar, Anand; et al.
Abstract : Background: Normothermic ex vivo kidney perfusion (NEVKP) has shown promising results for preservation, assessment, and reconditioning of kidney allografts in preclinical studies. Here, we report the first North American safety and feasibility study of deceased donor kidneys grafts transplanted following preservation with NEVKP. Methods: Outcomes of 13 human kidney grafts that received 1 to 3 h of NEVKP after being transported in an anoxic hypothermic machine perfusion device were compared with a matched control group of 26 grafts that were preserved with anoxic hypothermic machine perfusion alone. Results: Grafts were perfused for a median of 171 min (range, 44–275 min). The delayed graft function rate in NEVKP versus control patients was 30.8% versus 46.2% ( P = 0.51). During the 1-y follow-up, no differences in postoperative graft function, measured by serum creatinine, necessity for dialysis, and urine production, were found between the study group and the control group. There were no differences in 1 y posttransplantation graft or patient survival between the 2 groups. Conclusions: Our study demonstrates the safety and feasibility of NEVKP for human deceased donor kidney transplantation. Further studies are warranted to explore how this technology can minimize cold ischemia, improve posttransplant graft function, and assess and repair expanded criteria kidney grafts. Abstract :